Translation, development, and validation of the Arabic version of the SLEEP-50 questionnaire - AlAhmady, Nada F.; AlMojaibel , Abdullah A.; Purayidathil , Tunny S.; AlQurashi , Yousef D. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The SLEEP-50 is a comprehensive questionnaire consisting of 50 items, aimed at screening for a wide range of sleep disorders within the general population. This tool is particularly useful for identifying sleep-related issues that often go undiagnosed but significantly impact daily functioning and quality of life. Given its comprehensive nature, the SLEEP-50 can be utilized in both clinical and research settings to screen for potential sleep disorders and aid in early detection. By focusing on the most prevalent sleep issues, it allows healthcare professionals to make more informed decisions about further diagnostic assessments and interventions. Translating the SLEEP-50 questionnaire into different languages, such as Arabic, is highly important for several reasons such as cultural and linguistic barriers, especially with non-English speaking population. The need for an Arabic version of the SLEEP-50 is further underscored by the limited availability of validated sleep assessment tools in the region. Therefore, the aim of this study was to translate the SLEEP-50 scale into the Arabic language and review it for content and face validity following the scale development steps.Methods: The content validity assessment of the Arabic language version of the Sleep-50 scale consisted of three phases: (phase 1) translating the items from English to the Arabic language, (phase 2) judging the items for content validity, and (phase 3) judging the Arabic language Sleep-50 scale for face validity.Results: There was high agreement among seven experts who were invited to review the content of the Arabic version of the SLEEP-50 scale. Face and content validity showed high agreement among the targeted samples, which shows minimum correction because the translation was based on the pre-validated scale.Conclusions: The Arabic version of SLEEP-50 underscores the importance of cross-cultural adaptation in sleep medicine and highlights the need for similar efforts across other languages.